Characterization of PP/Mg(OH)(2) and PP/Nanoclay Composites with Supercritical CO2 (scCO(2)) - TAŞDEMİR, MÜNİR (TAYLOR & FRANCIS INC, 2011)
In this article, supercritical carbon dioxide (scCO(2)) is used to form a high density microcellular foam structure to reduce the polymer use and facilitate dispersion of Mg(OH)(2) and Nanoclay fillers. A twin-screw extruder system was used to predistribute the inorganic filler from the PP polymer, resulting composite PP/filler pellets. This followed by the use of a single-screw extruder wherein supercritical carbon dioxide is introduced in the formulation. Finally the resulting foam PP/filler/CO2 pellets are injection molded into test samples. The structure and properties of the composites are characterized using a scanning electron microscopy (SEM), Differential scanning calorimetry (DSC), and density measurements. Furthermore, PP/Clay/Mg(OH)(2) polymer composites are subjected to examinations to obtain their yield and tensile strengths, elasticity modulus, % elongation, Izod impact strength, hardness, Heat deflection temperature (HDT), Vicat softening point and Melt flow index (MFI).
Keywords: Cloisite 25A; Magnesium hydroxide; Polypropylene; Supercritical carbon dioxide; MICROCELLULAR FOAM; CARBON-DIOXIDE; NUCLEATION; EXTRUSION; MORPHOLOGY